Mosquitoes of the Marai Parai - Gurkha Hut, Kota Belud area, Ranau, Sabah, Malaysia - Natty Cassyendra Marakus; Hairul Hafiz Mahsol; Marcellus Nicholsonn -Sanai@Marcus; Azniza Mahyudin; Homathevi Rahman (Sabah Parks Nature Journal, 2024)
A mosquito study was conducted during the Marai Parai-Gurkha Hut Scientific Expedition at the Kota Belud area, Ranau, Sabah from 7th to 20th October 2023. The study aimed to record mosquito species along the trail from Marai Parai station to Gurkha Hut station, focusing especially species that have the potential to spread diseases to humans. Sampling sessions were conducted at three sampling sites: Kg Kiau Nuluh Basecamp, Nunuk Subcamp, and Marai Parai Subcamp. Mosquitoes were collected using standard approaches, including the Human Landing Catch (HLC) and Daytime Resting Collection techniques. A total of four genera of mosquitoes were recorded from Kg Kiau Nuluh Basecamp and Nunuk Subcamp, with Aedes albopictus (16.67%, n = 7) and Armigeres subalbatus (16.67%, n = 7) being the most common species, followed by Aedes sp. (9.52%, n = 4), Anopheles aitkenii (9.52%, n = 4), Armigeres moultoni (9.52%, n = 4), and Armigeres giveni (9.52%, n = 4). Additionally, female mosquitoes were found to be predominant across all species. The findings from this study can serve as baseline data for further ecological studies and monitoring of vector control in the area.